ANALISIS STRATEGI E-MARKETING INDIHOME UNTUK MENINGKATKAN PENJUALAN PADA PT TELKOM INDONESIA KANDATEL DENPASAR SELATAN - GUSTI AYU KADE LUXY ARYANTINI; I MADE WIDIANTARA (Universitas Mahasaraswati K. Mataram, 2023)
One of the most critical activities in business is marketing. With the development of technology, marketing strategies are not only done conventionally, marketing is also done online or often referred to as e-marketing. The importance of companies using e-marketing to compete and increase sales. This study analyzes IndiHome e-marketing strategy at PT Telkom Indonesia Kandatel Denpasar Selatan to increase sales. This research uses qualitative methods. Data were collected through observation, interviews, and documentation. This study uses the SWOT analysis method to determine the condition of the company. The results of this study are the total Internal Factor Analysis Summary (IFAS) score of 3.09 on Strengths and weaknesses. External Factor Analysis Summary (EFAS) score of 2.52 on opportunities and threats. Based on the results of the SWOT diagram analysis, the company is in the first quarter position and the company supports an aggressive growth policy. (Growth Oriented Strategy). The 4P e-marketing mix strategy is used in creating IndiHome e-marketing strategy to increase sales by improving product quality, price, distribution channels, and online promotions.